Mesenchymal Stromal Cells for Treatment of Acute Steroid‐Refractory Graft Versus Host Disease: Clinical Responses and Long‐Term Outcome. (13th October 2015) - von Dalowski, Felix; Kramer, Michael; Wermke, Martin; Wehner, Rebekka; Röllig, Christoph; Alakel, Nael; Stölzel, Friedrich; Parmentier, Stefani; Sockel, Katja; Krech, Mathias; Schmitz, Marc; Platzbecker, Uwe; et al.
Abstract: Acute graft‐versus‐host disease (aGvHD) remains a major cause of morbidity and mortality after allogeneic hematopoietic stem cell transplantation. Steroid‐resistant aGvHD is associated with poor outcome, and no commonly accepted salvage therapy is available for its treatment. Here, we report 58 adult patients treated with mesenchymal stromal cells (MSCs) as salvage therapy for steroid‐refractory aGvHD. Third‐party MSCs expanded in platelet lysate‐containing medium were transfused at a median dose of 0.99 × 10 6 cells per kg b.wt. A median of two MSC infusions were administered to each patient. Median time between the onset of aGvHD and the first infusion of MSCs was 12 days (range, 6–62 days). Most patients (79%) had grade IV aGvHD. Five patients showed complete response, five showed very good partial response, 17 showed partial response, and 31 showed no response. The estimated probability of survival after 1 year was 19%, and median survival was 69 days. Overall survival was not significantly different from that of a historical cohort of patients receiving alternative salvage therapy and no MSC infusions. In conclusion, MSC treatment on top of conventional immunosuppression was associated with an overall response rate of 47% but improved outcome in terms of survival remains to be shown. Stem Cells 2016;34:357–366